Mild Thermal Pre-treatment as a Method for Increasing the Methane Potential of Food Waste - Fadzil, Farihah; Fadzil, Farizah; Sulaiman, Siti Mariam; Shaharoshaha, A’isyah Mardhiyyah; Seswoya, Roslinda (International Information and Engineering Technology Association (IIETA), 2020)
It is challenging to manage the organic fraction of municipal solid waste (OFMSW) because it is putrescible. OFMSW is dominated by food waste, and food waste is easily degradable and causes unpleasant odor at the landfill. Anaerobic digestion was preferable for food waste stabilization. However, the methane production of food waste was low. This research aims to analyze the methane yield and its kinetics from the digestion of thermally treated food waste. In preparing the thermally treated food waste, the water bath at 50°C was used and operated for two hours. The biochemical methane potential (BMP) was conducted in a batch reactor. The reactor was operated at a mesophilic temperature at inoculum to substrate ratio of 2.0. The results showed that the ultimate methane yield of thermally treated food waste increased with 630 mL CH4/g VS higher than untreated food waste. The thermal pre-treatment improved the methane production rate with an increment of 9.8%. Besides, kinetic parameters observed from Modified Gompertz modeling were found lesser than laboratory observation. Despite that, thermal pre-treatment at 50°C significantly improved the digestion of food waste.